Evaluation of Articular Cartilage Injury Using Computed Tomography With Axial Traction in the Ankle Joint. (September 2018) - Nakasa, Tomoyuki; Ikuta, Yasunari; Sawa, Mikiya; Yoshikawa, Masahiro; Tsuyuguchi, Yusuke; Ota, Yuki; Kanemitsu, Munekazu; Adachi, Nobuo
Background: Although chondral or osteochondral injuries are usually assessed by magnetic resonance imaging, its accuracy can be low, presumably related to the relatively thin cartilage layer and the close apposition of the cartilage of the talus and tibial plafond. We hypothesized that axial traction could provide a contrast between the articular cartilage and joint cavity, and it enabled the simultaneous evaluation of cartilage and subchondral bone. The purpose of this study was to assess the feasibility of using computed tomography (CT) imaging with axial traction for the diagnosis of articular cartilage injuries. Methods: Chondral lesions in 18 ankles were evaluated by CT with axial traction using a tensioning device and ankle strap for enlargement of the joint space of the ankle. CT was done in 3-mm slices and programmed for gray scale, and then CT images were allocated colors to make it easier to evaluate the cartilage layer. The International Cartilage Repair Society (ICRS) grades on CT were compared with those on arthroscopic findings. Results: The respective sensitivity and specificity of CT imaging with traction using ICRS grading were 74.4%, and 96.3%. The level of agreement of the ICRS grading between CT images and arthroscopic findings was moderate (kappa coefficient, 0.547). Adding axial traction to CT increased the delineation of the cartilage surface, including chondral thinning, chondral defect, and cartilage separation. Conclusions: CT with axial traction produced acceptable levels of sensitivity and specificity for the evaluation of articular cartilage injuries, in addition to the assessment of subchondral bone. Level of Evidence: Level III, comparative case series.